Pengaruh Brand Personality dan Brand Experience Terhadap Brand Love Pada Flowa Bouquet (Studi pada Konsumen Flowa Bouquet di Kota Malang) - Choirunnisa Adinda Nuraini; Yulis Nurul Aini; Fullchis Nur Tjahyani (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Increasingly fierce competition in the floristry industry is driving businesses to build strong brands in order to attract and retain customers. Flowa Bouquet is a florist business in Malang, the sales in Flowa Bouquet fluctuated during August to December 2025, suggesting that consumer brand love has not been estabilished. This study aims to investigate and analyse the influence of brand personality and brand experience on brand love amongst Flowa Bouquet’s customers in Malang. This study applied a quantitative research method. The purposive sampling was used to obtain 97 Flowa Bouquet customers who had purchased the product at least once, determined using Cochran’s formula. The data were collected via a questionnaire and analysed using multiple linear regression analysis with the equation Y = a + b1X1 + b2X2, as well as hypothesis testing. The results of the correlation analysis between brand personality and brand experience on brand love showed that the calculated F-value was greater than the critical F-value—specifically, 67.389 > 3.093—with a coefficient of determination of 0.580. It means that brand personality and brand experience accounted for 58% of the variation in brand love, while the remaining variation was influenced by other factors not discussed in this study. Based on the research results, it can be concluded that brand personality and brand experience together have a positive and significant effect on brand love among Flowa Bouquet consumers. It is recommended that Flowa Bouquet maintain and enhance the aesthetic appeal of its brand personality and continuously strengthen the consumer experience in order to build and maintain customer brand love.